Visualisation of LCA environmental impacts of electrical and electronic products using multidimensional scaling. (18th February 2010) - Gutierrez, Ester; Adenso-Diaz, Belarmino; Lozano, Sebastian; Barba-Gutierrez, Yolanda
The growing amounts of waste electrical and electronic equipment may cause serious damage to the environment and have adverse effects on human health. This paper illustrates the wide-ranging applicability of the concept of environmental performance applied to a variety of household appliances, using multidimensional scaling (MDS) to compare them and visualise their positioning. LCA environmental impact assessment is measured using Eco-indicator 99. The results indicate the existence of significant differences as regards the environmental performance of appliances. Moreover, the assessed environmental performance of products changes when their relative economic value is taken into account. The results are intended to show the potential use of MDS as a method to analyse environmental impact data, providing consumers and producers with a synthetic description of the environmental impacts of appliances as well as information on the relative positioning of products in terms of their environmental performance.